Pengelolaan Limbah Industri PT. Apac Inti Corpora Bawen Semarang - Indriana Dwi Mutiara Sari (Jurnal Cakrawala Hukum, 2018)
The enactment of Law No. 32 of 2009 on the Protection and Management of the Environment, which states that managing and protecting the environment needs to be done as well as possible, based on the benefits provided by the environment itself. The industrial waste pollution phenomenon in Bawen, Semarang had threaten the sustainability of the environment functions. Environmental pollution due to industrial waste disposal will interfere the quality of people’s lifes and can degrade the quality of the environment on an ongoing basis. The problem of this research is how the waste procedure, PT. Apac Inti Corpora manages its waste disposal and its obstacles.Based on this research, known that PT. Apac Inti Corpora is using the Central Java Provincial Regulation No. 5 of 2012 on the Amendment of the Central Java Provincial Regulation No. 10 of 2004.How to cite item: Sari, I. (2018). Pengelolaan Limbah Industri PT. Apac Inti Corpora Bawen Semarang. Jurnal Cakrawala Hukum, 9(2), 186-194. doi:https://doi.org/10.26905/idjch.v9i2.2773